Clinical Application of Fully Covered Self-Expandable Metal Stents in the Treatment of Bronchial Fistula - Cao, Ming; Zhu, Qiang; Wang, Wei; Zhang, Tian Xiao; Jiang, Min Zhong; Zang, Qi (The Thoracic and Cardiovascular Surgeon, 2016)
Background The study was designed to access the feasibility, safety, and efficacy of fully covered self-expandable metal stents in the treatment of bronchial fistula.Methods Clinical data of nine patients (seven males and two females) who were treated with placement of tracheobronchial or bronchial fully covered self-expandable metal stents from August 2005 to November 2011 were analyzed retrospectively. Among these patients, seven were diagnosed with bronchopleural fistula, one with tracheopleural fistula, and one with left main bronchoesophageal fistula. Eight had accompanying thoracic empyema. The fistula orifices ranged from 3.5 mm to 25 mm in diameter. All patients received topical anesthesia. L-shaped stents were placed in six patients and I-shaped stents in three under fluoroscopic guidance. After stent placement, patients with empyema were treated with pleural lavage.Results Stent placement in the tracheobronchial tree was successful in all patients, without procedure-related complications. The operating time was 5 to 16 minutes. A small amount of bubble overflowed from the intrathoracic drainage tube of only one patient. In the other patients, the bubble in the intrathoracic drainage tube disappeared immediately or angiography showed no overflow of contrast agent from the fistula orifice. The effective rate of fistula orifice closure after stent placement was 100%, with 88.9% rated as excellent. One patient coughed the stent out 5 days after placement and hence a new stent was placed. Among the patients with empyema, one died of septicemia arising from empyema on day 8 and another died of brain metastases of lung cancer 6 months after stent insertion with persistent empyema. In the other six patients, empyema resolved after 2 to 5 months (cure rate 75%). Seven patients were followed up for 3 to 36 months. During follow-up, one stent was removed 8 months after implantation due to difficult expectoration, without recurrent empyema. The remaining patients tolerated the stents well. The stents remained stable without migration or empyema recurrence, and they could eat and drink well.Conclusion The use of fully covered self-expandable metal stents is a safe, effective, and fast minimally invasive method to treat bronchial fistula, especially for selected cases with empyema.
Keywords: bronchial fistula; fully covered self-expandable metal stents; empyema